Trans-Synaptic Spread of Amyloid-β in Alzheimer’s Disease: Paths to β-Amyloidosis - Annabella Pignataro; Silvia Middei (Neural Plasticity)
Neuronal activity has a strong causal role in the production and release of the neurotoxic β-amyloid peptide (Aβ). Because of this close link, gradual accumulation of Aβ into amyloid plaques has been reported in brain areas with intense neuronal activity, including cortical regions that display elevated activation at resting state. However, the link between Aβ and activity is not always linear and recent studies report exceptions to the view of “more activity, more plaques.” Here, we review the literature about the activity-dependent production of Aβ in both human cases and AD models and focus on the evidences that brain regions with elevated convergence of synaptic connections (herein referred to as brain nodes) are particularly vulnerable to Aβ accumulation. Next, we will examine data supporting the hypothesis that, since Aβ is released from synaptic terminals, β-amyloidosis can spread in AD brain by advancing through synaptically connected regions, which makes brain nodes vulnerable to Aβ accumulation. Finally, we consider possible mechanisms that account for β-amyloidosis progression through synaptically linked regions.